Efficacy and safety of traditional Chinese medicine for erosive oral lichen planus: A protocol for systematic review and meta analysis. Issue 48 (25th November 2020) - You, Yanyan; Huang, Xiaojin; Chen, Yunhui; You, Yu
Abstract: Background: Oral lichen planus (OLP) is a common disease among oral mucous membrane diseases. Erosive oral lichen planus (EOLP) is a type of OLP, it has a potential tendency of cancerization. There have been some randomized controlled trials (RCTs) using Traditional Chinese Medicine (TCM) to treat EOLP. No systematic review on the RCTs of TCM for EOLP has been reported, so we would propose a study protocol that aims to evaluate the evidence the efficacy and safety of TCM for treating patients with EOLP. Methods: The following databases from the inception to June 30, 2020 electronically, including PubMed, EMBASE, Cochrane Library, Chinese National Knowledge Infrastructure, VIP, Wanfang database, China Biomedical Literature Database will be searched. RCTs that meet the pre-specified eligibility criteria will be included. RevMan software (V5.3) will be performed data synthesis following data extraction and publication risk assessment. Subgroup and sensitivity analysis will be performed according to the condition of included RCTs. The primary outcomes include visual analogy scale, laboratory immune indicators, and scores of oral lesions and signs. Additional outcomes are clinical effective rate, adverse event rate, and recurrence rate. The Grading of Recommendations Assessment, Development and Evaluation system will be used to assess the strength of the evidence. Results: This study will provide a well-reported synthesis of RCTs on the efficacy and safety of TCM in the treatment of EOLP. Conclusion: This systematic review protocol will be helpful for providing evidence of whether TCM is an effective and safe therapeutic approach for patients with EOLP. Ethics and dissemination: Ethical approval is not necessary as this protocol is only for systematic review and it does not involve privacy data or conduct an animal experiment. This protocol will be disseminated by a peer-review journal or conference presentation. Systematic review registration: PROSPERO CRD42020172366.